99.8k views
1 vote
Please help me with these!!

Please help me with these!!-example-1

1 Answer

0 votes

Answer:

see explanation

Explanation:

(28)

2x³ - 32x ← factor out 2x from each term

= 2x(x² - 16) ← difference of squares

= 2x(x - 4)(x + 4)

(29)

3x² + 6x + 3 ← factor out 3 from each term

= 3(x² + 2x + 1) ← perfect square

= 3(x + 1)²

(30)


x^(4) - 81 ← difference of squares

= (x² - 9)(x² + 9) ← (x² - 9) is also a difference of squares

= (x - 3)(x + 3)(x² + 9)

(31)

5
x^(5) - 15
x^(4) + 10x³ ← factor out 5x³ from each term

= 5x³(x² - 3x + 2)

= 5x³(x - 1)(x - 2)

User Thbonk
by
5.1k points